PERAN PEMBIAYAAN MUSYARAKAH TERHADAP USAHA KECIL DAN MENEGAH PETANI DI KABUPATEN LAMONGAN (Study Kasus BPRS MADINAH LAMONGAN) - Noer Adillah Rohmania (EKPI 16 UMY 113, 2016)
*113 This research aims at finding out how the development of farmers’ business in Lamongan Regency is, and turnover and profit difference before and after the musyarakah financing at Sharia Public Financing Bank (BPRS) Madinah Lamongan. This research is a descriptive quantitative. The population in this research is the customers of the Small and Medium Enterprises (UKM) with musyarakah financing at Sharia Public Financing Bank (BPRS) Madinah Lamongan by involving 50 respondents. The analysis technique used in this research is Validity Test, Reliability Test, and T-test Sampling. The research finding shows that Sharia Public Financing Bank (BPRS) Madinah Lamongan has positive role toward the development of farmers’ Small and Medium Enterprises (UKM) in Lamongan Regency. There are turnover and profit differences before and after the musyarakah financing at Sharia Public Financing Bank (BPRS) Madinah Lamongan. Keywords: The Development of Farmers’ Business in Lamongan, Sharia Public Financing Bank (BPRS), Turnover, Profit.